Minimum wage development in the Russian Federation - Anna Bolsheva (International Labour Organization (ILO), 2012)
The aim of this paper is to analyze the effectiveness of the minimum wage policy at the national level in Russia and its impact on living standards in the country. The analysis showed that the national minimum wage in Russia does not serve its original purpose of protecting the lowest wage earners and has no substantial effect on poverty reduction. The national subsistence minimum is too low and cannot be considered an adequate criterion for the setting of the minimum wage. The minimum wage does not have significant impact on wage bargaining, but it does affect the wages of public workers. The study analyzed government, trade unions and employers' standpoints the setting of the minimum wage, and it concluded that there is no clear view within the country concerning the impact of the minimum wage on the economy. The legal mechanism for minimum wage determination is quiet sufficient, but in order to make the minimum wage an effective mechanism for preventing a decline in living standards and guarantee the lowest wage earners a decent standard of living, trade unions need to increase their power and draw up a comprehensive position on minimum wage setting. This position should include reconsideration of the current minimum wage criteria, the adjustment mechanism, regional differences, and the impact of the minimum wage on wage bargaining.
Keywords: 330; minimum wage; collective bargaining; trade union attitude; Russian Federation